Friction and wear behaviors of a high nitrogen austenitic stainless steel Fe-19Cr-15Mn-0.66N - Qiao Y.-X.; Sheng S.-L.; Zhang L.-M.; Chen J.; Yang L.-L.; Zhou H.-L.; Wang Y.-X.; Li H.-B.; Zheng Z.-B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The friction and wear behaviors of a Fe-19Cr-15Mn-0.66N high nitrogen austenitic stainless steel (HNSS) were investigated. Tribological investigations were carried out under different applied loads of 5 N, 10 N, 15 N, and 20 N. Scanning electron microscope (SEM) and laser scanning confocal microscope (LSCM) were used to understand the wear mechanisms under different loads and the reasons for the improved wear resistance. The lower friction coefficient and improved wear resistance were observed with the increase in applied loads. Under a higher load, the friction enhanced the work hardening ability of HNSS, which in turn improved its surface hardness and thus the increased wear resistance of HNSS.